Local enhanced site in surface enhanced infrared absorption with gold nano particle array by Rigorous coupled-wave analysis. (25th November 2020) - Mitobe, Daichi; Suzuki, Yushi; Shimada, Toru
Abstract: Surface enhanced infrared absorption (SEIRA) is a phenomenon by which infrared absorption of molecules adsorbed onto metal evaporated films is greatly enhanced. To clarify the enhancement mechanism in the evaporated films, we simulated the distribution of the enhancement field between Au nano-square columns by rigorous coupled wave analysis (RCWA). No maximum enhancement was observed on the particle surface. This result demonstrates that the first layer effect is not dominant for the increase in this system of columns. Furthermore, the enhanced field oscillates periodically between the particles. This periodic oscillation is not plasmon behavior seen in the visible region. Results indicate the existence of enhancement mechanisms other than plasmons and indicate the possibility that the interference effect enhances infrared absorption.